Reasons for Not Choosing Accounting Profession – Behavioral and Normative Conviction - Mardiana Mardiana; Michelle Kurniawan; Oei Venny Febrianti (Jurnal Akuntansi)
Purpose - Career choice among students is a crucial factor influencing career success and industry development. Accounting is one of the frequently chosen professions; however, there is a trend showing that some students tend to avoid this field. To understand this phenomenon in greater depth, this study aims to analyze how students' beliefs affect their thought patterns, attitudes, and subjective norms in the context of career choice, and to understand the reasons behind their tendency to avoid choosing an accounting profession at a private higher education institution, using the Theory of Reasoned Action (TRA) as the analytical framework. Design/methodology/approach - This research approach is quantitative, and the data used in this study were collected through the distribution of questionnaires. Surveys were electronically sent to third and final-year students among 100 students at private higher education institutions in West Java over a period of two months. Findings - The results confirmed the simplified TRA model and indicated that behavioral beliefs (such as difficulties with accounting and higher salaries in other professions) and normative beliefs (such as parental influence), through individual attitudes and subjective norms, affect students' decisions to pursue a career in accounting at certain private higher education institutions. The findings suggest that accounting programs at some private higher education institutions should have initiatives to encourage students to develop an interest in accounting, such as recruiting professional accountants as practitioners to provide motivating activities and assist students in learning more about the field. Research limitations/implications – Additionally, more practical information should be included in accounting courses, along with effective teaching strategies, and internships and required courses should be incorporated into the college curriculum and actively shared on social media.